PENGARUH SEPULUH EKUITAS MEREK TERHADAP MINAT BELI DAN KEPUTUSAN PEMBELIAN SEPATU BATA BERDASARKAN SIKAP KONSUMEN - Ambar Rukmi Dyah Kusumawardani; Jono M. Munandar; Mukhamad Najib (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Abstract. Bata shoes was the first top brand Indonesia in 2015-2017,  however, Bata’s selling rate come through decreased. The purpose of this study was to analyze brand equity ten influence towards purchase intention and purchase decision. Technique of sampling method in this research was quota purposive sampling. Total sample size was 200 respondents. Data were analyzed using descriptive statistic and Structural Equation Model (SEM) version 3.2.1 SMART PLS. This study shows that purchase intention of hedonistic consumers is influenced by brand awareness, brand associations, and brand loyalty. Purchase intention has influence on current purchase and future purchase. Current purchases of hedonistic consumers has influence on future purchases. Purchase intention of utilitarian consumers is influenced by perceived quality and brand loyalty. Meanwhile, purchase intention affects current purchase. In addition, future purchases of utilitarian consumers is influenced by current purchases. Thus, the results of this research would benefit to PT Bata, Tbk as considerating on formulating strategy of strong brand building in increasing sale and facing market competition